Associação e memória em The moons of Jupiter, de Alice Munro - Alves, Narayana Anunciato [UNESP] (2010)
This thesis aims to demonstrate that the unifying central point of the short stories Chaddeleys and Flemings and The Moons of Jupiter, from the volume The Moons of Jupiter, by Alice Munro, is the use of associations that link the return to the past through the narrative of the adult protagonist, who retells some facts occurred in childhood and those related to family life. In this trajectory, what is revealed is the women's conflict by seeking other roles than that of wife and mother. The narrative strategies used by the Canadian author to achieve this result are founded in the use of memory by her characters. To show how that works in Munro's text, Freudian studies are used in the analysis, emphasizing the work of the unconscious force manifested in the exercise of anamnesis of the protagonist-narrator.